Changes in breast volume during normal menstrual cycle and after oral contraceptives. Issue 5995 (29th November 1975) - Milligan, D; Drife, J O; Short, R V
Abstract : The volume of the left and right breasts was measured daily in four nulliparous women during normal menstrual cycles and after the use of oral contraceptives. Breast volume increased significantly in the second half of both normal and contraceptive-controlled cycles. The mean total change in volume throughout the cycle was 100 ml under natural conditions and 66 ml on oral contraceptives.